Understanding Pure Mathematics - Sadler A. J; Thorning D. W. S (Oxford University Press, 1998)
This book covers in one volume all topics required in the pure mathematics section of single subject A-Level Mathematics syllabuses. Introductory, Functions, Vectors, Coordinate Geometry, Trigonometry, Algebra, Matrices, Permutations and Combinations, Series and the Binomial Theorem, Probability, Calculus I: Differentiation, Sketching Functions, Calculus II: Integration, Calculus III: Further Reading, Trigonometry, Coordinate Geometry, Three-Dimensional Work: Vectors and Matrices, Algebra, Eponential and Logarithmic Functions, Numerical Methods, Answers, Index.